n Ontogenetiese studie van die vrug en saad van Sclerocarya birrea (A. Rich.) Hochst. subspesie caffra (Sond.) Kokwaro - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1984.